A modified superantigen rescues Ly6G− CD11b+ blood monocyte suppressor function and suppresses antigen-specific inflammation in EAE. (June 2013) - Slaney, Clare Y.; Toker, Aras; Fraser, John D.; Harper, Jacquie L.; Bäckström, B. Thomas
<x xml:space="preserve">Abstract</x> In a previous study, we showed that the Ly6G− CD11b+ blood monocytes residing in naïve mice are intrinsically immunosuppressive and that loss of this suppressive function may contribute to the development of autoimmunity in experimental autoimmune encephalomyelitis (EAE), a murine model of human multiple sclerosis. Here we report that mice treated with a modified superantigen coupled to myelin oligodendrocyte glycoprotein 35–55 (MOG35–55) peptide (DM-MOG35–55) suppressed the development of EAE. The treatment was associated with impaired MOG35–55-specific T cell proliferation and a decrease in IL-17 and IFNγ production in the draining lymph nodes. Analysis of circulating blood immune cells showed that the suppressor function of Ly6G− CD11b+ blood monocytes was reduced in EAE mice, but was restored in mice treated with DM-MOG35–55. Importantly, adoptive transfer of blood CD11b+Ly6G− cells isolated from DM-MOG35–55-treated mice protected recipient mice from developing EAE. Together, these results show that DM coupled to the auto-antigen MOG35–55: 1) suppresses EAE via antigen-specific suppression of T cell responses, and 2) re-establishes suppressor function of Ly6G− CD11b+ blood monocytes. Auto-antigens coupled to DM could therefore represent a new therapeutic approach for controlling inappropriate inflammation in autoimmune diseases such as multiple sclerosis by inducing antigen-specific T cell suppression.